Association Between Dry Eye and Sleep Quality in an Elderly Chinese Population in Taiwan: The Shihpai Eye Study - Tsai, Su-Ying; Kuang, Tung-Mei (Vision Science and Eye Health Journal, 2025)
Introduction: Dry eye symptoms often do not align with test results, and discrepancies between symptoms and clinical signs are common. Interestingly, dry eye symptoms correlate more with non-ocular conditions than clinical signs. Purpose: Our study explored the link between dry eye symptoms, signs, and sleep quality among the elderly. Methods: This community-based cross-sectional survey targeted vision and eye diseases in non-institutionalized individuals aged 65 and older. It began with a structured questionnaire on dry eye symptoms and the Pittsburgh Sleep Quality Index (PSQI), followed by a standardized ophthalmic examination, including slit lamp and dry eye tests. Results: Frequent dry eye symptoms were significantly associated with poor sleep quality (OR: 1.92; 95% CI: 1.36-2.70). Positive dry eye symptoms with tear break-up time ≤ 10 sec (OR: 1.78; 95% CI: 1.25-2.52) and a Schirmer test ≤ 5mm (OR: 1.61; 95% CI: 1.10-2.34) were linked to poor sleep quality, as was having meibomian gland disease (OR: 1.60; 95% CI: 1.09-2.32). Dry eye symptoms were also associated with the use of sleeping medication (OR: 1.41; 95% CI: 1.01-1.95). Subjects with dry eye symptoms and tear break-up time ≤ 10 sec (OR: 1.59; 95% CI: 1.13-2.22) or a Schirmer test score ≤ 5mm (OR: 1.46; 95% CI: 1.01-2.08) were more likely to use sleeping medication. Conclusions: Our study showed dry eye, especially dry eye symptoms, significantly impacts subjective sleep quality and the use of sleeping medication in the elderly. The causal relationship between sleep quality and dry eye requires further investigation.